GUGURNYA PENUNTUTAN ATAS GRATIFIKASI YANG DILAPORKAN KEPADA KOMISI PEMBERANTASAN KORUPSI - Trie Ayu Sudarti; Syamsuddin Muchtar; Abdul Asis (Jurnal Ilmu Hukum, 2018)
The study aims to analyze the existence of Article 12B UURI PTPK about gratuities that considered bribes and to analyze the reason of the removal of prosecution against recipients who reported the gratification to the KPK. This research used the normative methods. A gratuity or a reward become a criminal act of bribe when a organizer of the state or the civil servants receive gratification from any party relating to his position or occupation and not reported to KPK within 30 (thirty) days. The Report of acceptance of gratification to KPK by an organizer or state civil servants causing the removal of the state’s authority to prosecute the concerned of a criminal act of corruption.